Ape and essence : A Novel - Deese, R. S., 1964- (Oakland, California : University of California Press, 1949)
"We Are Amphibians tells the fascinating story of two brothers who changed the way we think about the future of our species. As a pioneering biologist and conservationist, Julian Huxley helped to advance the "modern synthesis" in evolutionary biology and played a pivotal role in founding UNESCO and World Wildlife Fund. Julian Huxley's argument that we must accept responsibility for our future evolution as a species has attracted growing number of scientists and intellectuals, who now embrace the concept of "transhumanism" that he first outlined in the 1950s. Although Aldous Huxley is most widely known for his dystopian novel Brave New World, his writings on religion, ecology, and human consciousness were powerful catalysts for the environmental and human potential movements that grew rapidly in the second half of the twentieth century. While they often disagreed about the role of science and technology in human progress, Julian and Aldous Huxley both believed that the future of our species depended on a saner set of relations with each other and with our environment. Their common concern for ecology has given their ideas about the future of Homo sapiens an enduring resonance in the twenty-first century. The amphibian metaphor that both brothers used to describe humanity highlights not only the complexity and mutability of our species, but also our ecologically precarious situation"--Provided by publisher.
Introduction : the question of questions for mankind -- Late Victorians -- Twilight of Utopias -- Spiritual biology -- Ape and essence -- We are amphibians -- Epilogue : the future of our species.
Includes bibliographical references (pages 211-221) and index.
Keywords: Huxley, Julian, -- 1887-1975.; Huxley, Aldous, -- 1894-1963.; Human evolution; Human ecology